How Might We Raise Interest in Robotics, Coding, Artificial Intelligence, STEAM and Sustainable Development in University and On-the-Job Teacher Training? - Henze, Jannik; Schatz, Carina; Malik, Shalina; Bresges, André (Frontiers in Education, 2022)
Schools are searching for strategies to foster 4C competencies (Creativity, Cooperation, Communication and Critical Thinking) in children. Scientific Reasoning, Critical Thinking, and the ability to debunk myths are already important competencies that can be fostered with science education. How can we approach the majority of seventh grade students in a given school to create innovative approaches for the future, and leverage their skills in science, art and (digital) technology along the path? And are the teachers ready to guide them on this path? This article focuses on the questions: how did the teachers adopt both the STEAM approach, and the use of digital tools while being supervised by researchers and student teachers and how did this change their beliefs about technology in education. As a pathway, we aimed to connect Robotics, Coding, Artificial Intelligence (AI) with the Sustainable Development Goals (SDGs) of the United Nations. Currently, SDGs are implemented into national policies and school curricula "as a universal call to action to end poverty, protect the planet, and ensure that by 2030 all people enjoy peace and prosperity" (United Nations Development Programme, 2021). With this, citizens, teachers, and governments alike struggle with strategies on how these goals can be reached by 2030, facing the growing challenges in an ever increasingly complex and insecure world. It is clear that technology will take a dominant role in this development. Based on the STEAM paradigm and the 5E approach of the Biological Sciences Curriculum Study (BSCS), we have developed a pedagogical concept that encompasses both the technological aspects, AI and the Sustainable Development Goals. We tested this concept as part of an on-the-job teacher training project with 60 education science student teachers and 8 teachers in their classrooms, together with their 116 7th grade students and found out that STEAM-based projects with a sixth phase in addition to the 5E approach can be carried out promisingly with the help of digital creativity tools. We found that the 5E model with an additional sixth phase is well suited for bringing STEAM into the classroom.